Genetic basis of silk resistance (antibiosis) to the corn earworm in six croáes of maize lines: statistical methodology - Bondari, K.=700 1 Wiseman, B.R.
Sumario (En)
Ilus.; 23 ref.
Keywords: ZEA MAYS; FITOMEJORAMIENTO; ANTAGONISMO; METODOS; HELICOVERPA; CONTROL GENETICO